PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA SKPD (Survei pada SKPD di Kota Palu) - Subhan, Subhan (Katalogis, 2017)
The aims of the study are: 1) to determine partial influence of leadership styles, compensation, and work enviroment on official’s performance in Palu City; 2) to determine simultaneous influence of leadership styles, compensation, and work enviroment on official’s performance in Palu City.The study intends to verify the relationship between variables by involving 77 respondents who were selected through purposive sampling method. The results conclude that: 1) variables of leadership styles, compensation, and work enviroment simultaneously have influence on official’s performance with signifficance of 0.000; 2) coefficient determinant shows adjusted R square of 0.359 that indicates that 35.90% of official’s performance in influenced by leadership styles, compensation, and work enviroment, while the rest is influenced by other variables that are not studied; 3) artial test shows that leadership styles, compensation, and work enviroment have signifficant influence on official’s performance with signifficant value of 0.004, 0.001, and 0.023 respectively.